Living in darkness: rural poverty in Venezuela - Leonardo Maldonado (Journal of Applied Economics, 2023)
ABSTRACTThis paper uses nighttime lights imagery and gridded population datasets to estimate 2000–2020 rural poverty rates for Venezuela at the state and municipality levels. Then, I examine if there has been a significant change in rural poverty during the economic collapse ongoing since 2013–2014. The main finding reveals that most of the Venezuelan territory experienced a considerable increase in rural poverty rates between 2014 and 2020. Furthermore, I confirm how new rural poor areas appear across the country in clusters, surrounding municipalities with moderate to high poverty rates. This suggests that in recent years, more Venezuelans have sunk in darkness.